Sistem Informasi Buku Induk Siswa Berbasis Web Di SD Negeri Tegalrejo No. 66 Surakarta - Liberta, Winona Namida; Naury, Chairullah; Wibowo, Kresno Ario Tri (Politeknik Harapan Bangsa Surakarta, 2023)
System personal data recording Tegalrejo Public Elementary School No. 66 Surakarta is still deep manual work. This matter done by handwriting about the information personal deep students a book large, then archived and attached to the main book previous years. So the problem is less efficient moment in writing, such as risk happen book keeping errors large in shape vulnerable paper against damage, loss and requires large storage space. In addition, also seek data students need quite a long time. There is a Information System Student Main Book Based on Web. This designed to facilitate the work of school operators in school administrative management. In process system development, this research using SDLC (System Development Life Cycle) method Waterfall model, PHP (Hypertext Preporocessor) programming language, Bootstrap Framework, MySQL (My Sequel Structured Query Language) database as well as Visual Studio Code as a means to design the system information. The results of research are presented in the form of an information system that can help manage administration at Tegalrejo Public Elementary School No. 66 Surakarta is with this information system, management of student master books becomes easier, concise, effective, and fast, searching for student data is easier, and also reduces the use of storage space for student master books. The percentage of 80% of the system can be implemented properly.